Single Phase AC Current Controller by Using Hysteresis Method - Zulkhairi; Facta Mochammad; Andromeda Trias; Hermawan; Setiawan Iwan (E3S Web of Conferences, 2019)
Generally, the electrical power supply acts as a voltage source only but many applications, current sources are needed. In conventional methods, to provide a current source, an electric power supply with variable voltage is adjusted to give the amount of current. In some electrical applications and devices, there is a demand to have a constant voltage with a variable current. This paper proposes a single phase alternating current controller as a power supply with a current source that can be adjusted using the hysteresis method. The advantage of the hysteresis method is that the electric current can follow changes in setting values and have a good response to any changes in the load given. This method, the actual current can follow the reference flow as needed. During testing, the inverter has succeeded in producing 3 Ampere 50 Hz at the output voltage of 50 Volt which is sent to the load. In applications, the proposed power supply is useful as an inverter to convert DC current into AC current. Furthermore, this proposed inverter has the opportunity as a renewable energy resource converter to convert direct current from photovoltaic to alternating current for various electronic devices in industries and households.